2019
DOI: 10.31788/rjc.2019.1215002
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Doped Slaked Lime as Adsorbent for the Removal of Basic Dyes

Abstract: A new eco-friendly green synthesized silver nanoparticles doped slaked lime was developed as an adsorbent for the removal of basic dyes from aqueous solution. Silver nanoparticles were synthesized through a green route using pomegranate peel and doped with slaked lime. Its applicability in removing basic green 4 dye from aqueous solution was evaluated in a batch process. The effect of control variables such as initial dye concentration, adsorbent dose, pH, agitation time and temperature on the removal of basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Filter failure may occur when such soil areas are subjected to conditions of heavy loading as a result of degradation of the soil's physical condition caused by pore-clogging (De Vries 1972). From this perspective, the comprehensive understanding of the factors that mainly affect treatment performance in the design of wastewater disposal areas and the need for adopting performance-based management strategies is gaining increasing recognition (Dawes & Goonetilleke 2003;Sheeja et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Filter failure may occur when such soil areas are subjected to conditions of heavy loading as a result of degradation of the soil's physical condition caused by pore-clogging (De Vries 1972). From this perspective, the comprehensive understanding of the factors that mainly affect treatment performance in the design of wastewater disposal areas and the need for adopting performance-based management strategies is gaining increasing recognition (Dawes & Goonetilleke 2003;Sheeja et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Even worse, it is also reported that the worldwide industrial effluent estimated 280,000 tons of textile dyes are being discharge every year [2]. The existence of dyes and paints from various industries such as textiles, plastics, cosmetics, food and petroleum refineries contain heavy loads of mixed colours from its discharged effluent that reflect toxicity to aquatic life [3]. Moreover, the presence of dyes in wastewater provide significant source of water pollution because even at low concentration the dye waste is visible and can harm aquatic life [4].…”
Section: Introductionmentioning
confidence: 99%